2012
DOI: 10.1063/1.3700963
|View full text |Cite
|
Sign up to set email alerts
|

Tuning minority-carrier lifetime through stacking fault defects: The case of polytypic SiC

Abstract: Minority-carrier lifetime is one of the key parameters governing the performance of semiconductor devices. Here, we report on tuning the minority-carrier lifetime through stacking fault (SF) defects in polytypic SiC. The SFs are distinguished in terms of their characteristic luminescence peaks at 482 nm, 471 nm, and 417 nm, respectively. Different from general point, linear, and volume defects, the planar SFs demonstrate the interesting phenomena of either decreasing or increasing the minority-carrier lifetime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…In this context, we investigate stacking faults (i.e. polytypic inclusions in 4H-SiC) as an intrinsic quantum well forming mechanism 3537 , and the effects that these structures have on divacancy defect (two adjacent empty atomic sites) color centers in their vicinity.
Fig. 2Common SiC polytypes and structure of a stacking fault in 4H-SiC. a – c show the primitive cells, the stacking sequences, and the possible divacancy nonequivalent configurations in 4H, 6H, and 3C-SiC, respectively.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, we investigate stacking faults (i.e. polytypic inclusions in 4H-SiC) as an intrinsic quantum well forming mechanism 3537 , and the effects that these structures have on divacancy defect (two adjacent empty atomic sites) color centers in their vicinity.
Fig. 2Common SiC polytypes and structure of a stacking fault in 4H-SiC. a – c show the primitive cells, the stacking sequences, and the possible divacancy nonequivalent configurations in 4H, 6H, and 3C-SiC, respectively.
…”
Section: Resultsmentioning
confidence: 99%
“…2b) inclusion in a 4H-SiC crystal 37,38 . It has been shown that such stacking faults form quantum-well-like states that have been observed through photoluminescence (PL) 3537 measurements in which the 6H in 4H polytypic inclusion was typically identified using the 482 nm PL-emission line 37 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 lists the experimental and theoretical results of phase transformation in SiC under different conditions. Since the 3C polytype introduces a quantum well (QW) structure in the 4H structure [4,8,37], energy would be gained through electrons entering the QW-related states, which is energetically favourable for the 4H ! 3C phase transformation during high-temperature annealing (>1000°C) [23,38].…”
Section: Resultsmentioning
confidence: 99%
“…Lifetime decrease with nitrogen doping, not correlating with the Z 1/2 trap density, was also observed in [7]. The recombination mechanisms when intrinsic Z 1/2 trap density is negligibly low are often attributed to surface recombination, dislocations and stacking faults [8][9][10][11]. Few works also indicate that other point defects cannot be neglected [2,12].…”
Section: Introductionmentioning
confidence: 96%